Physicians’ Understanding and Practices of Pharmacovigilance Qualitative Experience from a Lower Middle-Income Country - Hussain, Rabia; Hassali, Mohamed Azmi; Rehman, Anees ur; Muneswarao, Jaya; Hashmi, Furqan (Universiti Sains Malaysia, 2020)
Developed countries have established pharmacovigilance systems to monitor the safety of medicines. However, in the developing world, drug monitoring and reporting are facing enormous challenges. The current study was designed to explore the challenges related to the understanding and practices of physicians in reporting adverse drug reactions in Lahore, Pakistan. Through the purposive sampling technique, 13 physicians were interviewed. All interviews were audio-recorded, transcribed verbatim, and analyzed for a thematic content analysis. The thematic content analysis yielded six major themes: (1) Familiarity with medication safety and adverse drug reaction (ADR) concept, (2) Knowledge about pharmacovigilance activities, (3) Practices related to ADR reporting, (4) Barriers impeding ADR reporting, (5) Acknowledgement of the pharmacist’s role, and (6) System change needs. The majority of the physicians were unaware of the ADR reporting system; however, they were ready to accept practice changes if provided with the required skills and training. A lack of knowledge, time, and interest, a fear of legal liability, poor training, inadequate physicians’ and other healthcare professionals’ communication, and most importantly lack of a proper reporting system were reported as barriers. The findings based on emerging themes can be used to establish an eective pharmacovigilance system in Pakistan. Overall, physicians reported a positive attitude towards practice changes, provided the concerned authorities support and take interest in this poorly acknowledged but most needed component of the healthcare system.